Effective Fenton-like degradation of the tebuthiuron herbicide by ferrocene functionalized g-C3N4 - Sánchez-Montes, Isaac; Carneiro Doerenkamp, Jussara; Núñez-de la Rosa, Yeison; Hammer, Peter [UNESP]; Rocha-Filho, Romeu C.; Aquino, José M. (Elsevier, 2023)
At the present time, proper treatments of water and wastewater stand as one of the main concerns of our society due to otherwise potential health and environmental problems. Thus, this work aimed to synthesize, characterize, and use graphitic carbon nitride (g-C3N4) functionalized with ferrocenecarboxaldehyde (Fc) to assess its performance in the oxidation of the tebuthiuron (TBT) herbicide by in situ chemical activation reaction using hydrogen peroxide (H2O2 – HP) or persulfate (S2O82− – PS) as oxidant under white light irradiation. For that, the TBT concentration as well as oxidant consumption and main products in the form of carboxylic acids and inorganic ions were monitored during the oxidation experiments. Morphological, structural, and electrochemical assays confirmed that Fc functionalized g-C3N4 (g-C3N4/Fc) was indeed obtained, showing the expected activation of the Fe(III)/Fe(II) redox pair. Using g-C3N4/Fc to activate HP and PS, a complete oxidation of TBT was achieved only when using HP under acidic conditions (pH 3, [g-C3N4/Fc] = 0.250 g L−1, [HP] = 1 mmol L−1), with a total HP consumption of 50% after 120 min of treatment. However, the degree of mineralization of the organic load was low; acetic and formic acid were the main carboxylic acids produced as well as nitrate ions, but far below the theoretical value of complete mineralization. The main oxidant species leading to TBT oxidation were the hydroxyl radical and, to lesser extent, the sulfate radical. The in situ activation process mediated by g-C3N4/Fc was also dependent on produced electrons to regenerate Fe(II) ions, especially when using HP.
Keywords: Carbon nitride; Fenton reaction; Heterogeneous catalysis; In situ chemical activation; Semiconductor